Pathological outcomes in women with cervical adenocarcinoma In Situ treated by conisation or conisation followed by hysterectomy - Li, Lan Ying; Song, Da Long; Sun, Xiao Ying; Li, Zhi Gang; You, Ke Li (Frontiers in Oncology, 2026)
ObjectiveThis study aimed to evaluate the pathological outcomes of conisation with or without subsequent hysterectomy in patients diagnosed with adenocarcinoma in situ (AIS) and grade 3 cervical intraepithelial neoplasia (CIN3), emphasizing the impact of margin status on residual disease and recurrence risk.MethodsA retrospective analysis was conducted on patients diagnosed with AIS and CIN3 who underwent loop electrosurgical excision procedure (LEEP) or cold-knife conisation (CKC) between January 2012 and December 2022. The pathological findings of conisation and subsequent hysterectomy, as well as recurrence rates in patients managed conservatively, were analyzed. Patients were followed for a minimum of 3 years, with recurrence defined as the detection of cervical intraepithelial neoplasia (CIN) through colposcopy.ResultsA total of 387 patients were included: 107 with AIS and 280 with CIN3. Hysterectomy was performed in 72.9% of AIS patients and 49.3% of CIN3 patients after conisation. Positive conisation margins were associated with a higher likelihood of residual disease in hysterectomy specimens, especially in cases with cervical canal involvement in AIS (70.0%) and with combined endo/ectocervical and canal margin involvement in CIN3 (60.0%). In multivariable logistic regression analysis adjusting for age, HPV status, and conisation technique, cervical canal margin involvement was independently associated with positive hysterectomy pathology in AIS (OR 6.962, 95% CI 1.393–34.794; p = 0.018), whereas endo/ectocervical margin involvement was the independent predictor in CIN3 (OR 6.790, 95% CI 1.683–27.387; p = 0.007). The preoperative HPV infection rate was lower in AIS than in CIN3 (88.8% vs 97.1%, p = 0.002).ConclusionWhile hysterectomy is recommended for AIS with positive margins, conisation alone may be a safe alternative for selected patients without involvement of the cervical canal margin.